Geology and Correlative Analysis of Borehole Logs with Geo-electric Sections of Some Parts of Ibadan, Southwestern Nigeria - Ajibade, Olumuyiwa Michael; Ariyo, Stephen Oluwafemi; Oladipupo, Seun Damola; Okeleye, Abiola Omolabake (Iraqi Journal of Science, 2022)
The property of rocks varies from one geological location to another or even disappears laterally, and these properties are important factors in determining groundwater quantity. This makes this research work focused on the correlative analysis of lithologies and borehole logs with geo-electric sections in the basement terrain of Ibadan, southwestern Nigeria, using Borehole logging and geophysical electrical method. Twenty-two vertical electrical sounding stations and borehole Logsare acquired within the study area with a maximum Schlumberger electrode separation of 100m. The data are interpreted qualitatively and quantitatively by partial curve matching and computer iteration to obtain the first-order geo-electric model parameters. The results of the geo-electric investigation reveal some lithological Layers such as topsoil, clay, weathered laterite basement, and fresh basement. At the same time, those from boreholes include topsoil, loamy soil, friable brown soil, clayey-sand, sandy-clay, laterite weathered basement/saprolite, and Fresh Basement. Electrical resistivity and borehole logs correlation revealed: poor, poor-moderate and moderate-perfect correlations based on a comparison between the number of lithological layers encountered from both vertical electrical sounding derived lithology and those from borehole and depth of occurrence. The depth of water struck grouped into three 0 - 45 m, 45 - 70 m, and 50 - 100 m to bring out the most favourable depth of aquifer potential while three yields categories 0.5-2 lt/s; 2 - 4lt/s and 4 -12 lt/s are observed with the above depth classification respectively. Good yielding fractures increase with depth in the quartzite regions but decrease with depth in both gneisses and the schist rock bodies. The correlations between geo-electric sections and borehole logs have shown that the geoelectric section obtained from the vertical electric section cannot totally be substituted for borehole logging but can serve as alternative means of classifying the sub-surface lithologies in the absence of borehole logging.